Anatomical considerations for obturator nerve block with fascia iliaca compartment block. Issue 9 (28th April 2021) - Bendtsen, Thomas Fichtner; Pedersen, Erik Morre; Moriggl, Bernhard; Hebbard, Peter; Ivanusic, Jason; Børglum, Jens; Nielsen, Thomas Dahl; Peng, Philip
Abstract : This report reviews the topographical and functional anatomy relevant for assessing whether or not the obturator nerve (ON) can be anesthetized using a fascia iliaca compartment (FIC) block. The ON does not cross the FIC. This means that the ON would only be blocked by an FIC block if the injectate spreads to the ON outside of the FIC. Such a phenomena would require the creation of one or more artificial passageways to the ON in the retro-psoas compartment or the retroperitoneal compartment by disrupting the normal anatomical integrity of the FI. Due to this requirement for an artificial pathway, an FIC block probably does not block the ON.